414 Prognostic factors related to recurrence and survival of early stage vulvar squamous cell carcinoma. (13th November 2020) - Wang, Y; Lindemann, K; Bruheim, K; Barrameda, A; Davidson, B; Skeie-Jensen, T
Abstract : Objection: To evaluate prognostic factors for recurrence and survival among patients with early stage vulvar squamous cell carcinoma (VSCC). Methods: This is a retrospective study of patients with clinical stage I VSCC who were treated at Oslo University Hospital – Radium hospital between 01.01.2006 and 31.12.2016. Clinicopathological characteristics, treatment and follow-up were extracted from the medical records. Univariate and multivariate analysis were used to identify prognostic factors for recurrence, time to recurrence (TTR) and overall survival (OS). A p-value of <0.05 was considered to be statistically significant. Results: 133 patients who underwent primary vulva surgery and evaluation of groin lymph node status were included. The median age was 64 years, and groin lymph node metastases were identified in 22.6% of patients. The median follow-up time was 67 months (range 5–165). The 5-year recurrence and survival rates were 23.3% and 72.2%, respectively. In multivariate analysis, the presence of lichen sclerosus and groin lymph node metastasis were independent prognostic factors for recurrence and TTR, with an odds ratio (95% CI) of 5.37 (2.13–13.53) and 2.8 (1.17–6.72) for recurrence, and a HR (95% CI) of 2.6 (1.35–5.19) and 2.2 (1.13–4.26) for TTR, respectively. Age >70 years and a history of recurrence were independent prognostic factors for OS, with a HR (95% CI) of 3.0 (1.58–5.65) and 2.1 (1.57–6.15), respectively. Conclusions: Patients with lichen sclerosus and groin lymph node metastasis have a higher risk for recurrence and shorter TTR. Patients with age >70 years and a history of recurrence have significantly poorer OS.